Fatty acid metabolism and the basis of brown adipose tissue function. (2nd April 2016) - Calderon-Dominguez, María; Mir, Joan F.; Fucho, Raquel; Weber, Minéia; Serra, Dolors; Herrero, Laura
ABSTRACT: Obesity has reached epidemic proportions, leading to severe associated pathologies such as insulin resistance, cardiovascular disease, cancer and type 2 diabetes. Adipose tissue has become crucial due to its involvement in the pathogenesis of obesity-induced insulin resistance, and traditionally white adipose tissue has captured the most attention. However in the last decade the presence and activity of heat-generating brown adipose tissue (BAT) in adult humans has been rediscovered. BAT decreases with age and in obese and diabetic patients. It has thus attracted strong scientific interest, and any strategy to increase its mass or activity might lead to new therapeutic approaches to obesity and associated metabolic diseases. In this review we highlight the mechanisms of fatty acid uptake, trafficking and oxidation in brown fat thermogenesis. We focus on BAT's morphological and functional characteristics and fatty acid synthesis, storage, oxidation and use as a source of energy.